Wadiah Yad Dhamanah: an implementation analysis in Muamalat Bank Berhad / Muhammad Fauzan Janal - Janal, Muhammad Fauzan (2019)
This research aims to analyze the implementation of savings products using Wadiah Yad Dhamanah contract. This study was conducted to study its implementation in Bank Muamalat Berhad. This is because the implementation of Wadiah Yad Dhamanah has become more limited and has been eradicated. In addition, the problem with the Wadiah Yad Dhamanah contract is that the customer is still unclear about the detailed implementation and still cannot distinguish the Wadiah Yad Dhamanah and conventional savings. The purpose of this first research is to identify Wadiah Yad Dhamanah from an Islamic perspective. The second is to analyze the implementation of Saving-i products at Bank Muamalat Berhad. In addition, data collection is a qualitative method of document analysis and semi-structured interviews. The present findings show that Wadiah Yad Dhamanah is a product that is in accordance with shariah guidelines. There is no element of interest, uncertainty and gambling in this contract as it would be similar to a conventional deposit.